(3SjchdhLjI eQVi GdEjORs (3GdJYQja(B- (3GdhHGFjGJ(B- (3GdCSHGH(B- (3GdOjfGejGJ(B- (3GdhbGjI(B- (3GdYdGL h GdEQTGO ef NdGd OQGSGJ ejOGfjI Ydi eQVi GdEjORs - (3ZGfe, eMeO MSfs ((3GdbGgQIs (3OGQ ZQjHs, 2008)
(3jbOe gPG GdcJGH HQfGeLkG EQTGOjkG ddJYGed eY eQVi GdEjORs
(3bGFeI HHdjhLQGajI(B: (3U(B. 299- 312s
4 11
Keywords: (3GdEjORs